2022
DOI: 10.3389/fpubh.2022.929683
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Workload, Personality, and Psychological Flexibility on Occupational Stress Among Medical Staff: A Fuzzy-Set Qualitative Comparative Analysis

Abstract: ObjectiveDuring the COVID-19 pandemic, the occupational stress of medical staff has been a major issue. This study aimed to suggest a new strategy to identify high-risk factor sets of occupational stress in medical staff using fuzzy-set qualitative comparative analysis (fs-QCA) and provide ideas for the prevention and intervention of occupational stress.MethodsA total of 1,928 medical staff members were surveyed and tested using the Acceptance and Action Questionnaire-II (AAQ-II), Occupational Stress Inventory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…This finding can be said to confirm that occupational stress adversely affects mental health and decreases job-related performance and satisfaction. This result concurs with the research suggesting that psychological distress such as depression and anxiety is triggered by occupational stress, that it has a negative correlation with psychological flexibility and that it reduces job performance and job satisfaction (Liberman et al, 2002;Reed, 2016;Devi and Lahkar, 2021;Aldaiji et al, 2022;Quan et al, 2022). Stress can be said to be a psychological problem which influences performance and satisfaction under any circumstances.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding can be said to confirm that occupational stress adversely affects mental health and decreases job-related performance and satisfaction. This result concurs with the research suggesting that psychological distress such as depression and anxiety is triggered by occupational stress, that it has a negative correlation with psychological flexibility and that it reduces job performance and job satisfaction (Liberman et al, 2002;Reed, 2016;Devi and Lahkar, 2021;Aldaiji et al, 2022;Quan et al, 2022). Stress can be said to be a psychological problem which influences performance and satisfaction under any circumstances.…”
Section: Discussionsupporting
confidence: 89%
“…The concepts of meaning in life and psychological flexibility are the two main facets of positive psychology. Quan et al (2022) found an opposite directional relationship between psychological flexibility and psychological distress in the workplace. It was also revealed by another study that there were significant relationships between job satisfaction and burnout and psychological flexibility and that psychological flexibility had an effect on mental flexibility and psychological distress (Chong et al, 2023).…”
Section: Psychological Flexibility and Meaning In Life As Mediatorsmentioning
confidence: 92%
See 1 more Smart Citation
“…To investigate occupational stress, stress response, and resilience among subjects, a Chinese version of the instrument called the revised edition of the occupational stress inventory (OSI-R) proposed by Oispow was used [ 29 ]. This questionnaire comprises the Occupational Roles Questionnaire (ORQ), Personal Stress Questionnaire (PSQ), and Personal Resources Questionnaire (PRQ).…”
Section: Methodsmentioning
confidence: 99%